The Association of Chiari Type III Malformation and Klippel-Feil Syndrome with Mirror Movement: A Case Report - Erol, Fatih Serhat; Ucler, Necati; Yakar, Huseyin (Turkish Neurosurgical Soc, 2011)
Basically Chiari type III malformation is a combination of encephalocele with of brain stem and cerebellar abnormality. Although Klippel-Feil syndrome may be associated with other congenital anomalies, this syndrome is mainly associated with varying degrees of cervical vertebral fusion anomalies. In this study, we reported the association of Chiari type III malformation and Klippel-Feil syndrome with the mirror movement by imaging studies. The main involvement in Chiari type III malformation and Klippel-Feil syndrome is in the craniocervical junction. In such a small area, the emergence of these complex pathologies in our case was remarkable. Our patient had reconstruction surgery of the posterior fossa and his encephalocele was excised successfully. Hydrocephaly and/or deterioration in the functions of other posterior fossa structures have not been seen in the patient's follow-up.
Keywords: Chiari type III malformation; Klippel-Feil syndrome; Mirror movement; Syringomyelia; Craniocervical region